The Role of Teachers in Fostering the Values of Religious Moderation in Junior High Schools - Nadiah, Sofi; Nurkamelia Mukhtar; Aslamiah, Soibatul; Fadhli Zulmi; Sriwahyuni (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2023)
Religious moderation is the process of understanding and practicing religious teachings in a fair and balanced manner. Religious moderation teaches us how to view our religious life properly and correctly, not being extreme or radical. Religious moderation also tells us as Muslims to be tolerant among fellow religious followers, not to discriminate between races, ethnicities, or religions, and also teaches us how to think dynamically and innovatively. This study aims to analyze the role of Islamic Religious Education teachers in fostering the values ​​of religious moderation, such as the values ​​of tasamuh (compassion), musawah (compassion), and tahadhur (compassion) in junior high schools. This study uses a descriptive qualitative method, with data sources collected through individual interviews. The research findings indicate that, first, the role of Islamic Religious Education teachers in fostering the values ​​of tasamuh (compassion) and religious moderation in junior high schools is as a teacher as a demonstrator, a teacher as a class manager, and a teacher as a mediator. Second, the role of Islamic Religious Education teachers in fostering the values ​​of musawah (compassion) and religious moderation in junior high schools is as a teacher as a demonstrator, a teacher as a motivator, and a teacher as a mediator. Third, the role of Islamic Religious Education teachers in fostering the values ​​of religious moderation in junior high schools is as a demonstrator, a motivator, a mediator, and an evaluator.